The Impact of Antarctic Ice Microalgae Polysaccharides on D-Galactose-Induced Oxidative Damage in Mice - Yi, Ruokun; Deng, Lei; Mu, Jianfei; Li, Chong; Tan, Fang; Zhao, Xin (Frontiers in Nutrition, 2021)
Antarctic ice microalgae (Chlamydomonas sp.) are a polysaccharide-rich natural marine resource. In this study, we evaluated the impact of Antarctic ice microalgae polysaccharides (AIMP) on D-galactose-induced oxidation in mice. We conducted biological and biochemical tests on tissue and serum samples from mice treated with AIMP. We found that AIMP administration was associated with improved thymus, brain, heart, liver, spleen, and kidney index values. We also found that AIMP treatment inhibited the reduced aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, superoxide dismutase, glutathione peroxidase, and glutathione levels as well as the increased serum, splenic, and hepatic nitric oxide and malondialdehyde levels arising from oxidation in these animals. Pathological examination revealed that AIMP also inhibited D-galactose-induced oxidative damage to the spleen, liver, and skin of these animals. AIMP was additionally found to promote the upregulation of neuronal nitric oxide synthase, endothelial nitric oxide synthase, cuprozinc-superoxide dismutase, manganese superoxide dismutase, catalase, heme oxygenase-1, nuclear factor erythroid 2-related factor 2, γ-glutamylcysteine synthetase, and NAD(P)H dehydrogenase [quinone] 1 as well as the downregulation of inducible nitric oxide synthase in these animals. High-performance liquid chromatography analysis revealed AIMP to be composed of five monosaccharides (mannitol, ribose, anhydrous glucose, xylose, and fucose). Together, these results suggest that AIMP can effectively inhibit oxidative damage more readily than vitamin C in mice with D-galactose-induced oxidative damage, which underscores the value of developing AIMP derivatives for food purposes.